UPAYA MENINGKATKAN KONSENTRASI BELAJAR ANAK USIA 5-6 TAHUN MELALUI TEKNIK BICARA PELAN DI PAUD MAWAR CIAMPEL - Tri Sriyanpi, Imar; Sulaeman, Devi; Riyadi, Ahmad (Penerbit Lafadz Jaya, 2025)
Learning concentration is crucial in early childhood education, yet many children aged 5–6 years struggle to maintain focus, which hampers learning outcomes. This study aimed to enhance learning concentration through the application of the soft-spoken technique at PAUD Mawar Ciampel. Using Classroom Action Research (CAR) with qualitative and quantitative approaches, the study involved 13 Group B children (aged 5–6 years) and was conducted over two cycles consisting of planning, action, observation, and reflection. The soft-spoken technique was implemented to foster a calm, conducive environment, allowing children to better attend to teacher instructions. Data collection included participatory observation, photo and video documentation, and both quantitative (percentage concentration improvement) and qualitative (behavioral changes) analyses. Findings revealed a significant improvement in concentration: from 66% in the first cycle to 85% in the second. Positive changes were also noted in listening to instructions, task persistence, and maintaining calm during lessons. Most children reached the “Developing as Expected” (BSH) category based on PAUD assessment standards. These results indicate that the soft-spoken technique effectively improves learning concentration among children aged 5–6 years. The study suggests that educators incorporate this technique consistently and integrate it with complementary strategies to optimize outcomes in early childhood education.